Knowledge, attitudes, and practices of patients with recurrent pregnancy loss toward pregnancy loss - Mu, Fangxiang; He, Tianyu; Wang, Kexin; Wang, Fang (Frontiers in Public Health, 2024)
Objective Self-management is crucial in managing recurrent pregnancy loss (RPL). This study explored the knowledge, attitudes, and practices (KAP) of patients with RPL toward RPL. Methods This cross-sectional study was conducted among patients with RPL between January 2023 and June 2023 at the Second Hospital of Lanzhou University. Participants’ demographic characteristics and KAP were determined using a self-designed questionnaire (Cronbach’s α = 0.818). Structural equation modeling (SEM) was used to observe the correlations among KAP and different factors. Results This study analyzed 497 valid questionnaires. The mean knowledge, attitude, and practice scores were 11.59 ± 4.30 (possible range: 0–20, 57.95%), 44.17 ± 3.18 (possible range: 13–65, 67.95%), and 32.39 ± 5.22 (possible range: 8–40, 80.98%), indicating poor knowledge, moderate attitude, and proactive practice. Age was non-linearly associated with the KAP dimensions, with a positive impact of age on KAP among those aged <32 years old. Knowledge was directly influenced by education (β = 1.49, p < 0.001) and income (β = 1.08, p < 0.001). The attitude was directly influenced by knowledge (β = 0.25, p < 0.001) and indirectly influenced by education (β = 0.37, p = 0.001) and income (β = 0.27, p < 0.001). Practice was directly influenced by knowledge (β = 0.26, p < 0.001), attitude (β = 0.28, p < 0.001), and income (β = 0.68, p = 0.012), and indirectly influenced by knowledge (β = 0.07, p = 0.001), education (β = 0.59, p = 0.001), and income (β = 0.42, p < 0.001). Conclusion Women with RPL in Lanzhou show poor knowledge, moderate attitude, and proactive practice toward RPL. This study identified specific KAP items that would require improvements. The study also identified categories of patients who would need more attention.